Molecular characterization of Shewanella and Aeromonas isolates associated with spoilage of Common carp (Cyprinus carpio) - Beaz Hidalgo, Roxana (2015)
Storage in ice is a common way of preserving commercial fish species but some microorganisms can still contaminate and participate in the spoilage of the product; therefore, identification of potential harmful microbes is important. Thirteen colonies were isolated from common carp (Cyprinus carpio) that had been stored in ice, whose phenotypic identification revealed that they belonged to the genera Aeromonas (n = 5) and Shewanella (n = 8). Molecular genotyping with ERIC-PCR showed clonality only among two of the five Aeromonas isolates and for two groups (n = 3; n = 2) of the eight Shewanella isolates. Sequencing the rpoD gene showed that four Aeromonas isolates belonged to the species Aeromonas salmonicida and one to A. sobria. Of the eight Shewanella, seven isolates cluster with Shewanella putrefaciens and one with Shewanella profunda in the 16S rRNA phylogenetic tree. However, analysis of the gyrB gene showed that these eight isolates could constitute a new species closely related to S. baltica. The Shewanella and A. salmonicida isolates produce off-odours and reduce trimethylamine oxide, indicating that they might contribute to the spoilage of the fish.